Prevalence of Human Immunodeficiency Virus is psychiatric patients admitted in Mankweng Hospital - Makhomisane, Wisani (My University, 2023)
The prevalence of HIV in psychiatric patients has been studied in urban communities in South Africa but there currently appear to be no published studies concerning Limpopo and limited others focusing on rural communities in South Africa. This study set out to investigate the prevalence of HIV infection and associated factors in psychiatric patients admitted to Mankweng Hospital psychiatric ward. It looked at the prevalence of HIV infection in these psychiatric patients and the socio-demographic risk factors associated with HIV infection in these patients, and it explored the relationship between psychiatric diagnosis, compliance to treatment, and substance use with HIV infection among these patients. A retrospective chart review of 229 clinical files of adult patients admitted to Mankweng psychiatric hospital between 1 October 2018 and 30 September 2019 indicated that most of the patients had a diagnosis of schizophrenia (44.7%) or bipolar disorder (25.9%). It was found that only 88 files had HIV status recorded. This represented a 38.6% testing rate, thus 61.4% of the psychiatric patients did not have a known HIV status. Of those 88 patients who were tested, 52.2% were recorded as HIV positive, and the patients with bipolar disorders had a significantly higher number testing HIV-positive. The overall prevalence rate of 52.2% was considered to be disproportionally high. It was attributed to the very low HIV testing rate. It is recommended that efforts be made to improve HIV testing rates in this at-risk and vulnerable community. The low rate of testing was a limitation in this research
Thesis (M. Med. (Psychiatry)) -- University of Limpopo, 2023
Keywords: Human Immunodeficiency Virus; Psychiatric patients; Mankweng Hospital; Limpopo Province; South Africa; HIV (Virus) -- South Africa -- Limpopo Province; Psychiatric hospital patients -- South Africa -- Limpopo Province; Psychotherapy patients -- South Africa -- Limpopo Province